Effect of Achilles tendon mechanics on the running economy of elite endurance athletes - Pinto Souza, M.; Sánchez, C.; Martins, N.; Menegaldo, L. L.; Pompeu, F.; Fernandes de Oliveira, L. (International Journal of Sports Medicine, 2021)
The Achilles tendon stores and releases strain energy, influencing running economy. The present study aims to verify the influence of the Achilles tendon tangent modulus, as a material property, on running economy by comparing two groups of elite endurance-performance athletes undergoing different running training volumes. Twelve athletes, six long-distance runners and six pentathletes, were studied. Long-distance runners had a higher weekly running training volume (116.7±13.7 vs. 58.3±20.4 km, p<0.05) and a better running economy (204.3±12.0 vs. 222.0±8.7 O2 mL · kg-1 · km-1, p<0.05) evaluated in a treadmill at 16 km·h-1, 1% inclination. Both groups presented similar VO2max (68.5±3.8 vs. 65.7±5.0 mL · min-1 · kg-1, p>0.05). Achilles tendon tangent modulus was estimated from ultrasound-measured deformations, with the ankle passively mobilized by a dynamometer. True stress was calculated from the measured torque. The long-distance runners had a higher maximum tangent modulus (380.6±92.2 vs. 236.2±82.6 MPa, p<0.05) and maximum true stress than pentathletes (24.2±5.1 vs. 16.0±3.5 MPa, p<0.05). The correlation coefficient between tangent modulus at larger deformations was R=-0.7447 (p<0.05). Quantifying tendon tissue adaptations associated with different running training volumes will support subject and modality-specific workouts prescription of elite endurance athletes